2018
DOI: 10.1371/journal.pone.0206043
|View full text |Cite
|
Sign up to set email alerts
|

Sympatric and allopatric niche shift of endemic Gypsophila (Caryophyllaceae) taxa in the Iberian Peninsula

Abstract: Several species of the Gypsophila genus are endemic to the Iberian Peninsula, including gypsophytes of particular ecological, evolutionary and biochemical interest, and taxa that have undergone both sympatric and allopatric genetic differentiation. The niche shift among these taxa has been assessed using ecological niche modelling and ordination techniques, adopting a niche overlap approach to compare the similarity and equivalency of the ecological niches. We used the Maximum Entropy method to study the poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…It is important to note that this does not mean that G . bermejoi could reach those areas in the period of time contemplated, although historically there is strong evidence for migration and episodes of colonization for this and other related Gypsophila taxa [23, 72] . Indeed, it is difficult to establish whether or not these areas could be colonized by this plant within this time span (2070).…”
Section: - Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that this does not mean that G . bermejoi could reach those areas in the period of time contemplated, although historically there is strong evidence for migration and episodes of colonization for this and other related Gypsophila taxa [23, 72] . Indeed, it is difficult to establish whether or not these areas could be colonized by this plant within this time span (2070).…”
Section: - Discussionmentioning
confidence: 99%
“…Indeed, this is reflected in a recent detailed study comparing the bioclimatic niches of G . bermejoi and its parental taxa [23] .…”
Section: - Introductionmentioning
confidence: 99%
“…All these plants are gypsophytes endemic to the Iberian Peninsula, and they are of particular ecological, evolutionary and biochemical interest. Some evidence points to a recent origin of the current populations of G. bermejoi [42,43]. Indeed, based on ENMs and SDMs it has been shown that the parental taxa of G. bermejoi had a high degree of sympatry during the Last Glacial Maximum (LGM), although the climatic conditions may have repressed the formation of this species because of its very narrow bioclimatic niche at that time [42,43].…”
Section: Introductionmentioning
confidence: 99%
“…The new genetic architecture generated by hybridization can thus also facilitate ecological divergence, promoting a speciation process by exploiting a specific niche, e.g., ref. 42 .…”
mentioning
confidence: 99%